Design of Ultra-wideband Radar Signal Generator Based on RFSoC - Gu, Pengcheng; Tian, Xiao; Chen, Gang; Liu, Ge; Huang, Xiuqiong (2025 10th International Conference on Intelligent Computing and Signal Processing (ICSP), 2025)
Nowadays, Radar signal generator is widely used in complex electromagnetic environment construction and test of electronic warfare (EW). However, requirement of complex function, high performance and light weight meets difficult in realization. This paper discusses the development of an ultra-wideband radar signal generator based on Radio Frequency System on Chip (RFSoC). The paper raises a 3-domain algorithm to describe and generate radar signal. What's more, ultra-wideband signal generate algorithm and multiple signal generate algorithm. These algorithms are implemented in embedded software, which archive the advantage of boarder bandwidth, enough settable parameter, flexible software and more compact size, which solves the problems constructing radio frequency (RF) compact test and validation system, especially under desktop environment. Test performance for the proposed radar signal generator proves the capability. The instant bandwidth can reach more than 1GHz. The number of instantaneous generate signals can reach 4, which can play an important role in indoor test and validation.